Production of biogas from the waste of some restaurants of Tikrit University in order to produce thermal energy - et. al., Shareef Faiq Sultan Al-tikrity, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research, a study was undertaken to convert the waste of some Tikrit University restaurants into the energy that can be used in the production of electrical or thermal energy in addition to the disposal of that waste, which is a major problem facing the University of Tikrit. Therefore, the mechanism for disposing of these wastes was studied and converted into another form that can be used, where a system designed to dispose of these wastes. Where the best ratios of mixing were calculated to produce the largest amount of gas, as it was noted that the volume of biogas had increased to its highest value (3170 milliliters), and specifically when the water mixing ratio to wastes increased to (35%) and the highest value of the resulting biogas was On the 35th day of the system's operating time. After that, those wastes are used as organic compounds that are used as plant fertilizers that contain compounds rich in useful components for plants during cultivation. This research will include a presentation of the most important results obtained from the designed system. Also, this paper will discuss the most important practical results that have been measured in an experimental way in detail.